Childhood Maltreatment and Anhedonic Symptoms: Test of a Dual-risk Model in Emerging Adults - Cohen, Joseph R. (Journal of interpersonal violence, 2022)
Anhedonia, defined as deficits in positive affect and approach related behaviors, remains an understudied trauma response. As anhedonic responses to interpersonal violence are associated with a more severe course of psychopathology that is more difficult to treat, an increased focus on risk factors for anhedonia is necessary. The present study sought to address this gap in the literature by testing a theoretical model that highlights two transdiagnostic pathways leading to anhedonic responses in emerging adults attending college. Specifically, our study examined how childhood maltreatment subtypes (a) uniquely associate with depressive and post-traumatic stress (PTS) manifestations of anhedonia and (b) how temperament (i.e., anticipatory positive affect) and distress (i.e., negative mood) explain these relations. At baseline, a racially diverse sample of 462 emerging adults (AgeMean = 19.45; 75.5% female; 45.5% White) completed self-report forms on childhood abuse and neglect, anticipatory positive affect, negative mood, and anhedonia. Individuals completed measures of temperament and psychological distress again 6-weeks, and 12-weeks later. Latent growth curve models were utilized to test our model. Consistent with hypotheses, deficits in anticipatory positive affect uniquely explained the relation between neglect and depressive/PTS anhedonic symptoms. Meanwhile, negative mood mediated the relation between abuse and both forms of anhedonia. These findings support the theory that two separate risk pathways lead to anhedonia. Support for our model suggests that distinguishing between pathways for anhedonic responses may be the key to a more targeted, transdiagnostic, trauma-informed approach for treating and preventing these deleterious, treatment-resistant, internalizing symptoms.